Benign Paroxysmal Vertigo of Childhood. Video Recordings of Episodes. Issue 9 (27th October 2022) - Bertholon, Pierre; Mazzola, Laure; Gavid, Marie; Karkas, Alexandre; Peyron, Roland; Convers, Philippe
Abstract : Objectives: The main objective was to describe the nystagmus observed during benign paroxysmal vertigo (BPV) of childhood, which is one of the criteria included in the three versions of the International Classification of Headache Disorders that has never been specified. The secondary objectives were to emphasize the usefulness of a mobile phone to record nystagmus and discuss the physiopathology of this nystagmus. Patient: A 6-year-old boy complained of approximately 30 to 50 vertigo attacks, most of them lasting around 1 minute, during a 6-month period. Intervention: Otoneurologic history and examination, audiovestibular exploration, and brain imaging were performed between the attacks. Video recording by the parents' mobile phone and video electroencephalography recording during a 1-day hospitalization were performed during the episodes. Main Outcome Measure: Analysis of seven video recordings performed by the parents and four during a 1-day hospitalization, as well as follow-up. Results: The assessment between the attacks confirmed the diagnosis of BPV according to International Classification of Headache Disorders criteria. Video recordings constantly demonstrated a strong left horizontal nystagmus present at fixation in all direction of gaze, enhanced in left gaze. This nystagmus was associated with a rightward body deviation. Conclusion: The clinical presentation was more consistent with a peripheral vestibular deficit than with a central disorder. We encourage video recording of their child by the parents because it will help both to define the ictal nystagmus and to understand the underlying pathophysiology. The latter is discussed and is probably more complex than initially thought in BPV.